Strategies for effective teaching - Ornstein, Allan C. (Mandaluyong City, Philippines : National Book Store, 1992)
This book is written for all who are interested in learning how to teach or improve their teaching , as well as teaching students how to learn. It will help prepare novice teachers for their new roles, and provide seasoned teachers with new insights into what they are doing.
Chapter 1. Teaching and Learning -- Chapter 2. Classroom management and discipline -- Chapter 3. Testing students -- Chapter 4. Evaluating students -- Chapter 5. Instructional objectives -- Chapter 6. Instructional methods -- Chapter 7. Instructional materials -- Chapter 8. Instructional technology -- Chapter 9. Grouping for instruction -- Chapter 10. Instructional planning -- Chapter 11. The Effective teacher -- Chapter 12. Professional growth.
Includes bibliographical references and index.
Keywords: CLASSROOM MANAGEMENT